Expression and Prognostic Significance of PD-L2 in Diffuse Large B-Cell Lymphoma - Gu, Qianhui; Li, Jing; Chen, Zhuolin; Zhang, Jie; Shen, Hui; Miao, Xiaobing; Zhou, Ying; Xu, Xiaohong; He, Song (Frontiers in Oncology, 2021)
Recent studies suggest that programmed death ligand-2 (PD-L2) constitutes an important antitumor immune response. Here, we investigated the relationship between PD-L2 expression and clinicopathological features in diffuse large B-cell lymphoma (DLBCL). Immunohistochemistry showed that positive expression of PD-L2 was observed in 45 of 181 newly diagnosed patients, including 14 cases with expression exclusively on tumor cells (TCs), and 31 cases with the expression on both TCs and immune cells (ICs) in the tumor microenvironment (TME). In 21 recurrent patients, positive expression of PD-L2 was present in 6 cases, including 2 cases with expression exclusively on TCs, and 4 cases with the expression on both TCs and ICs in the TME. Patients with PD-L2 tumor proportion score (TPS) ≥ 1% exhibited a better ECOG performance status (PS) (ECOG PS score < 2, P = 0.041), lower international prognostic index (IPI) score (P < 0.001), and early Ann Arbor stage (Ann Arbor stage I or II, P = 0.010). Similarly, patients with PD-L2 immune proportion score (IPS) ≥ 1% also exhibited a better ECOG PS (ECOG PS score < 2, P = 0.006) and lower IPI score (P = 0.001). Survival analysis showed that patients with PD-L2 TPS ≥ 1% exhibited prolonged overall survival (OS) and progression-free survival (PFS). However, survival analysis showed no prognostic significance based on expression of PD-L2 on ICs in the TME. TC PD-L2 expression was significantly associated with OS (P = 0.041) and FPS (P = 0.001). In the multivariate analysis, TC PD-L2 expression was an independent prognostic risk factor for PFS (P = 0.013), but not for OS (P = 0.249). Furthermore, we found that higher TC and IC PD-L2 expression was associated with higher objective response rate (ORR). Moreover, we demonstrated that the expression level of PD-L2 was positively correlated with the expression status of M1 macrophage markers CD86 and CD68. Our findings highlight PD-L2 as a promising therapeutic target in DLBCL.